ANALISIS 3R PADA PEMBIAYAAN KREDIT PEMILIKAN RUMAH (Studi Bank Tabungan Negara Kantor Cabang Syariah Bogor) - Fitri Nur Anggraeni; Rully Trihantana; Ria Kusumaningrum (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2022)
This research is motivated by the frequent occurrence of arrears in the payment of mortgage customer housing loans (KPR). . One of the principles used by banks in assessing whether or not a prospective customer is feasible or not is the 3R analysis (Return, Repayment, Ability to Bear Risk). The purpose of this study was to analyze the 3R factors in the provision of mortgage financing to customers in a study at the State Savings Bank Bogor Sharia Branch Office (BTN KCS Bogor). The method used in this research is descriptive qualitative. The data collection method was carried out using observation, interview and documentation techniques at BTN KCS Bogor. The results of the study show that the 3R factor analysis has been used by BTN KCS Bogor to provide credit. And in the KPR financing assessment mechanism at BTN KCS Bogor using 3R analysis, each has a sharia basis, both taken from the Qur'an and Hadith.